A national standards-based assessment on functionality of electronic medical records systems used in Kenyan public-Sector health facilities. (January 2017) - Kang'a, Samuel; Puttkammer, Nancy; Wanyee, Steven; Kimanga, Davies; Madrano, Jason; Muthee, Veronica; Odawo, Patrick; Sharma, Anjali; Oluoch, Tom; Robinson, Katherine; Kwach, James; Lober, William B.
Abstract: Background: Variations in the functionality, content and form of electronic medical record systems (EMRs) challenge national roll-out of these systems as part of a national strategy to monitor HIV response. To enforce the EMRs minimum requirements for delivery of quality HIV services, the Kenya Ministry of Health (MoH) developed EMRs standards and guidelines. The standards guided the recommendation of EMRs that met a preset threshold for national roll-out. Methods: Using a standards-based checklist, six review teams formed by the MoH EMRs Technical Working Group rated a total of 17 unique EMRs in 28 heath facilities selected by individual owners for their optimal EMR implementation. EMRs with an aggregate score of ≥60% against checklist criteria were identified by the MoH as suitable for upgrading and rollout to Kenyan public health facilities. Results: In Kenya, existing EMRs scored highly in health information and reporting (mean score = 71.8%), followed by security, system features, core clinical information, and order entry criteria (mean score = 58.1% − 55.9%), and lowest against clinical decision support (mean score = 17.6%) and interoperability criteria (mean score = 14.3%). Four EMRs met the 60.0% threshold: OpenMRS, IQ-Care, C-PAD and Funsoft. On the basis of the review, the MoH provided EMRs upgrade plans to owners of all the 17 systems reviewed. Conclusion: The standards-based review in Kenya represents an effort to determine level of conformance to the EMRs standards and prioritize EMRs for enhancement and rollout. The results support concentrated use of resources towards development of the four recommended EMRs. Further review should be conducted to determine the effect of the EMR-specific upgrade plans on the other 13 EMRs that participated in the review exercise.